2014
DOI: 10.1111/jfb.12435
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lake minnow Eupallasella percnurus semen in relation to sperm morphology, regulation of sperm motility and interpopulation diversity

Abstract: Sperm morphology and regulation of sperm motility of lake minnow Eupallasella percnurus, an endangered cyprinid, were investigated. Milt characteristics from two isolated populations of E. percnurus were compared to characterize the interpopulation diversity. Electron microscopic studies revealed that E. percnurus spermatozoa comprise simple, uniflagellate, anacrosomal aquasperm with species-specific features as an eccentrically located implantation of nuclear fossa and eccentric insertion of flagellum. Sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In lake minnow ( Eupallasella percnurus ), the two populations analysed were markedly different in several sperm quality biomarkers such as milt volume, sperm concentration and sperm motility (Dietrich et al . ). As a result, authors estimated 134 million motile spermatozoa per ejaculate (volume × concentration × percentage of motility) in the ‘Siedliszcze’ population compared to 480 million motile sperm in males from ‘Guzy’ population.…”
Section: Fish Sperm Motility: a Useful Tool For Multidisciplinary Stumentioning
confidence: 97%
“…In lake minnow ( Eupallasella percnurus ), the two populations analysed were markedly different in several sperm quality biomarkers such as milt volume, sperm concentration and sperm motility (Dietrich et al . ). As a result, authors estimated 134 million motile spermatozoa per ejaculate (volume × concentration × percentage of motility) in the ‘Siedliszcze’ population compared to 480 million motile sperm in males from ‘Guzy’ population.…”
Section: Fish Sperm Motility: a Useful Tool For Multidisciplinary Stumentioning
confidence: 97%
“…Sperm motility characteristics were measured using a two-step procedure described by Wojtczak et al (2007) and modified by Dietrich et al (2014). Motility (MOT) and straight line velocity (VSL) were determined.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to morphology study, the analyses carried out revealed that the spermatozoa of the four species studied presented a morphology similar to that of other cyprinids and leuciscids with external fertilisation, with small sized cells, spherical head, a middle piece and uni agellate (Neznanova, 2012). The sperm morphology of other leuciscid and cyprinid species has been characterised, for example, in E. percnurus, where the sperm head is 1.88 µm long and 2.03 µm wide (Dietrich et al, 2014)…”
Section: Sperm Quantity and Qualitymentioning
confidence: 82%